Effect of Modulating Activity in the Right DLPFC on Revenge Behavior: Evidence From a Noninvasive Brain Stimulation Investigation - Zheng, Wanjun; Tao, Yuanping; Li, Yuzhen; Ye, Hang; Luo, Jun (Frontiers in Psychology, 2021)
Revenge is common in our daily lives, and people feel good when engaging in revenge behavior. However, revenge behavior is a complex process and remains somewhat of a puzzle of human behavior. Neuroimaging studies have revealed that revenge behaviors are associated with activation of a neural network containing the anterior cingulate cortex, ventral striatum, inferior frontal gyrus and dorsolateral prefrontal cortex (DLPFC). Recent brain stimulation research using transcranial direct current stimulation (tDCS) and transcranial magnetic stimulation has shown a causal relationship between brain regions and revenge behaviors, but the findings have been mixed. In the present study, we aimed to study whether stimulation in the DLPFC can change participants’ revenge behavior in conditions where participants’ wealth was taken away in different ways. We adapted the moonlighting game and designed a new paradigm. Our study revealed that revenge behavior increased following activation in the right DLPFC, suggesting that the right DLPFC plays an important role in overriding basic human impulses related to self-interest and retaliation. In addition, our results revealed that the right DLPFC is crucial in revenge behavior related to the motivation to invade.